Subjective impacts of computerized cognitive training for healthy older adults in the context of the COVID-19 pandemic - Cristiane Benedita Rodrigues da Mota Antunes Viviani; Tiago Nascimento Ordonez; Andreia Rodrigues Pereira; Karen de Souza Jardim; Jonatas da Hora Borges; Lais Aparecida Pereira Mota; Gabriela dos Santos; Ana Paula Bagli Moreira; Cássia Elisa Rossetto Verga; Graciela Akina Ishibashi; Guilherme Alves da Silva; Luiz Carlos de Moraes; et al. (Arquivos de Neuro-Psiquiatria)
Background Computerized cognitive training programs may have benefited the self-assessment of memory, quality of life, and mood among older adults during the coronavirus disease 2019 (COVID-19) pandemic.